Demographic Tipping Points as Early Indicators of Vulnerability for Slow-Breeding Megafaunal Populations - de Silva, Shermin; Leimgruber, Peter (Frontiers in Ecology and Evolution, 2019)
Decisions based on trends in population abundance and distribution may fail to protect populations of slow-breeding, long-lived megafauna from irrevocable decline if they ignore demographic constraints. For such taxa, we suggest that understanding the interactions among vital rates governing population growth rates be prioritized over predicting probabilities of extinction. The proximity of a population to the demographic tipping points, i.e. where growth rate switches from positive to negative, can signal vulnerability to perturbation long before numbers drop below a point of no return. We define the “demographic safe space” as the combination of key vital rates that support a non-negative growth rate and illustrate this approach for Asian elephants. Using modeling, we find that even with optimal reproduction, Asian elephant populations cannot tolerate annual female mortality rates exceeding 7.5%. If adult mortality is very low (3% / yr), populations can tolerate high annual mortality in calves below age 3 (up to 31.5% / yr), or slow female reproduction (primiparity at 30 years or average inter-birth interval of up to 7.68 years). We then evaluate potential impact of current threats, showing that near-optimal reproduction and high calf survival is necessary to offset even modestly increased mortality among adult female age classes. Rather than rely on simple counts or “viability” assessments, we urge that conservation resources for slow-breeding megafauna also be invested in identifying demographic tipping points and how to maintain populations within their safe spaces.